Production of an anticanine globulin (polyspecific) reagent for laboratory investigation - Sriwichai C. (2014)
Objectives: Canine allo- or autoantibodies are clinically important, but attachment of these immunoglobulin G (IgG) antibodies does not produce observable haemagglutination. Antibody to canine globulins is required to demonstrate sensitisation of red blood cells. Commercial reagents are available, but these often differ in sensitivity and specificity. Rabbit anticanine globulins (polyspecific) were produced for use in canine blood compatibility testing and in the investigation of immune-mediated haemolytic anaemia. Methods: Canine sera was pooled, IgG was purified and subsequently used to immunise rabbits. A rising titre of anticanine IgG was demonstrated by indirect enzyme-linked immunosorbent assay. Rabbit anticanine complement was isolated and investigated by agglutination of complement-coated canine red blood cells. Both antibodies were purified and checked for crossreactivity before being combined to polyspecific anticanine globulins. The obtained reagent was used to indicate sensitised canine red blood cells and free antibodies in three different types of clinical samples, including blood for compatibility testing and that for investigation of immune-mediated haemolytic anaemia and screening for post-transfusion alloantibodies and was also compared to commercial Coombs' reagent. Results: The product provided results in accordance with those from commercial Coombs' reagent. The sensitivity for canine crossmatching was 100% and specificity for diagnosing immune-mediated haemolytic anaemia was 87%. Clinical Significance: This product is helpful for canine crossmatching purposes and in the investigation of immune-mediated haemolytic anaemia. © 2011 British Small Animal Veterinary Association.